Analysis on non-stationary gyroscopes and their application in measurement technology - Andreev, A I; Perekrestov, A P (Journal of physics. Conference series, 2021)
In this work, the main subjects of research are: 1) analysis of the process of rotation of a Chinese top on a flat surface, 2) analysis of the main dependencies and an explanation of the rise of the center of gravity of the top during rotation due to nonlinear friction and the resulting force of the overturning top on the upper axis. Also, an analytical study of the motion of the top along the plane and the laws of rotation was carried out, the rotation of the top was analyzed from the point of view of asymmetry during rotation. The top-top spinning top is an interesting case of raising the center of gravity during rotation. The simplest model of a Chinese top can be a dynamic symmetric inhomogeneous ball, the center of mass of which lies on the axis of dynamic symmetry, but does not coincide with its geometric center. The precession of the Chinese top is based on dry friction. The occurrence of a gyroscopic deflection moment is based on the frictional force. Considering the simplest top-type top, one can distinguish the main forces acting on this body, as well as its characteristics that determine the precession. Based on this fact, it is possible to propose the use of this body of revolution as a working medium for instruments such as tribometers and gravimeters. In the first case, this makes it possible to increase the accuracy of the device, in the second, to create a new scheme for measuring gravitational fields. The relevance of this work is the analysis of the rotation of the Chinese top and the possibility of its use in measuring instruments.